PENGUATAN JIWA WIRAUSAHA SISWA SMK HANG NADIM MELALUI PELATIHAN KONTEN KREATIF DAN PROMOSI DIGITAL PRODUK KULINER DAN FASHION - Mauli Siagian; Wasiman Wasiman; David Humala Sitorus; Neni Marlina Br Purba (PUAN INDONESIA, 2026)
This community service activity aims to strengthen the entrepreneurial spirit of students at Hang Nadim Vocational High School through training and mentoring in creative content production and digital promotion of culinary and fashion products. The program was designed in response to the challenge of students’ limited digital promotion skills, which have resulted in a restricted marketing reach for their products. The implementation method employed a participatory approach encompassing needs analysis, theoretical and practical training in digital marketing, content creation mentoring, and outcome evaluation. The results indicate a significant improvement in participants’ understanding of digital promotion strategies and their ability to produce creative content for social media. Approximately 90% of the participants were able to create engaging and effective promotional content. The impact of this activity includes increased entrepreneurial motivation, enhanced creativity, and improved student competence in utilizing digital platforms for business development. Therefore, this program successfully fostered a spirit of digital entrepreneurship among students at Hang Nadim Vocational High School as preparation for facing future challenges in the creative economy.